Economic nationalism on the rise: Foreign direct investment in the USA after the Dubai fiasco - Jens van Scherpenberg (Stiftung Wissenschaft und Politik (SWP), 2006)
The failed takeover of the terminal port operations at six American sea ports by a Dubai company has cast a spotlight on growing economic nationalism in the United States. This could turn into a serious domestic problem for President Bush and the Republican Party by the midterm elections in November 2006. For several reasons, however, the newly rekindled American debate on how to deal with foreign direct investment is also a cause for concern on an international level. First, it reflects a growing tendency in the U.S. to implement restrictions on trade and capital flows under the banner 'national security;' even Europe-based companies cannot count on remaining unaffected. Second, such restrictions on FDI in the United States as currently considered in the Congress, curtail the usability of the immense dollar holdings that have accrued in states running trade surpluses with the U.S. That, in turn, can accelerate a flight out of dollar assets, thereby initiating the global adjustment crisis which has so far been avoided in spite of the US current account deficit's continual rise. And, third, the Dubai Ports debate is putting the relationship between America and its most valued Arab allies under heavy strain by discrediting their heretofore close political and economic ties with the U.S. (SWP-Comments / SWP)
Keywords: 320